Lucinid bivalves of Guadeloupe: diversity and systematics in the context of the tropical Western Atlantic (Mollusca: Bivalvia: Lucinidae) - Taylor, Ohn D.; Glover, Emily A. (Zootaxa, 2016)
Intensive sampling of molluscs from the intertidal to depths of 800 m around the islands of Guadeloupe in the Lesser Antilles (KARUBENTHOS 2012, 2015) recovered 25 species of Lucinidae. All the Guadeloupe species are described and illustrated including details of larval shells and the taxonomy revised within the context of the wider western Atlantic fauna and recent classifications. Concurrent molecular analysis has helped separate frequently confounded species. ‘Myrtea’ pristiphora is placed in the Leucosphaerine genus Myrtina previously known from the Indo-West Pacific. A second western Atlantic species of Callucina, C. pauperatus previously known from the Pliocene of Jamaica is recognised from the southern Caribbean and off Brazil. The deeper water species ‘Myrteopis’ lens is placed in Afrolucina previously known from the eastern Atlantic. Lucinids commonly identified as Ctena orbiculata are shown to belong to two distinct species, C. orbiculata in the Gulf of Mexico and Florida and C. imbricatula in the Caribbean. Epicodakia is recognised for the first time in the western Atlantic with E. pectinata widely distributed across the region and E. filiata recorded from deeper water. Three species of Lucina are recognised, Lucina pensylvanica in the Gulf of Mexico and Florida and the similar Lucina roquesana from the Caribbean and Bahamas while the smaller L. aurantia has a wide distribution from central America to the Bahamas. A new species of Parvilucina, P. latens is described; this is similar to P. pectinella but has an internal ligament. The long problematic species ‘Codakia’ cubana is assigned to Ferrocina. A new genus, Guyanella is introduced for Parvilucina clenchi the smallest known lucinid. A critical reassessment of the lucinid fauna of the western Atlantic Ocean identifies 46 species for the region with 33 of these living at depths less than 200 m. Deeper-water habitats have been much less investigated except at sites of hydrocarbon seeps. Some species are widespread throught the whole region but others have more restricted ranges. Notable are species pairs, for example of Ctena, Lucina, Lucinisca and Parvilucina that are either largely Caribbean or Gulf of Mexico/Floridian in distribution. Although extralimital, two problematic species from the mid-south Atlantic island of St Helena are refigured and placed in Cavilinga.